Cadmium-doped flexible perovskite solar cells with a low-cost and low-temperature-processed CdS electron transport layer. Issue 32 (3rd April 2017) - Tong, Guoqing; Song, Zihang; Li, Chengdong; Zhao, Yaolong; Yu, Linwei; Xu, Jun; Jiang, Yang; Sheng, Yun; Shi, Yi; Chen, Kunji
Abstract : Hybrid perovskite solar cells (PSCs) are promising candidates in exploring high performance flexible photovoltaics, where a low-temperature-processed metal oxide electron transfer layer (ETL) is highly preferable. Abstract : Hybrid perovskite solar cells (PSCs) are promising candidates in exploring high performance flexible photovoltaics, where a low-temperature-processed metal oxide electron transfer layer (ETL) is highly preferable. In this work, we demonstrate perovskite solar cells based on inorganic cadmium-sulfide (CdS) as the electron transfer layer, fabricated using low-temperature chemical bath deposition (CBD) at <85 °C. We show that natural Cd-doping has been achieved in the perovskite fabricated via a physical–chemical vapor deposition (P-CVD), which under properly controlled reaction and post-growth annealing leads to a high power conversion efficiency of 14.68% for the CdS-PSCs on glass substrate. Then, flexible perovskite solar cells with CdS as the ETL are fabricated for the first time and demonstrate a high PCE of 9.9%. These results highlight the exciting potential of a low-temperature-processed and readily scalable CdS-based PSC structure in the development of high performance flexible solar cells.